An Atomistic-Based Continuum Modeling for Evaluation of Effective Elastic Properties of Single-Walled Carbon Nanotubes. (16th March 2016) - Al-Kharusi, M. S. M.; Alzebdeh, K.; Pervez, T.
Abstract : The mechanical behavior of SWCNTs is characterized using an atomistic-based continuum method. At nanoscale, interatomic energy among carbon atoms and the corresponding force constants are defined. Subsequently, we used an atomistic finite element analysis to calculate the energy stored in the SWCNT model, which forms a basis for calculating effective elastic moduli. In the finite element model, the force interaction among carbon atoms in a SWCNT is modeled using load-carrying structural beams. At macroscale, the SWCNT is taken as cylindrical continuum solid with transversely isotropic mechanical properties. Equivalence of energies of both models establishes a framework to calculate effective elastic moduli of armchair and zigzag nanotubes. This is achieved by solving five boundary value problems under distinct essential-controlled boundary conditions, which generates a prescribed uniform strain field in both models. Elastic constants are extracted from the calculated elastic moduli. While results of Young's modulus obtained in this study generally concur with the published theoretical and numerical predictions, values of Poisson's ratio are on the high side.